2018
DOI: 10.2147/tcrm.s175581
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxychloroquine and risk of development of cancers: a nationwide population-based cohort study

Abstract: BackgroundHydroxychloroquine (HCQ), one of the disease-modifying antirheumatic drugs, may lead to an inhibition of autophagy. Autophagy, an intracellular self-defense mechanism for the lysosomal degradation of cytoplasmic components such as damaged organelles, plays a role in protecting against neoplasm growth but is also vital for cancer cells due to an increased intracellular metabolic waste.MethodsTaiwan National Health Insurance Database was subjected to analysis to investigate the effect of HCQ exposure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Common AEs associated with hydroxychloroquine use include gastrointestinal symptoms, headaches, and rashes [66]. There does not appear to be an elevated risk of malignancy with hydroxychloroquine use [67][68][69]. In fact, numerous preclinical models have shown that hydroxychloroquine can induce tumor suppression and may help overcome chemotherapy resistance [70].…”
Section: Hydroxychloroquinementioning
confidence: 99%
“…Common AEs associated with hydroxychloroquine use include gastrointestinal symptoms, headaches, and rashes [66]. There does not appear to be an elevated risk of malignancy with hydroxychloroquine use [67][68][69]. In fact, numerous preclinical models have shown that hydroxychloroquine can induce tumor suppression and may help overcome chemotherapy resistance [70].…”
Section: Hydroxychloroquinementioning
confidence: 99%
“…It prevents the accumulation of damaged proteins and organelles as a tumor suppressor, while also as a tumor promotor it facilitates tumor growth and aggressiveness by surviving microenvironmental stress. Fortunately, in a nationwide population-based cohort study, Mao et al showed that the use of HCQ was not associated with an increased risk of cancer in patients with autoimmune diseases (50). Nevertheless, it is obvious that further investigations in well-designed studies and large welldefined cohorts are required before more clear conclusions can be drawn.…”
Section: Safety and Possible Adverse Reactions Of Hcqmentioning
confidence: 99%